TEACHERS PROFESSIONAL DEVELOPMENT AT SMAN 1 MATAULI PANDAN TAPANULI TENGAH - Saleh, Irwan; Ali, Mukti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research was motivated by the relatively good professional development of teachers at SMA Negeri 1 Pandan Tapanuli Tengah. The purpose of this study is to determine the self-development carried out by teachers through the activities carried out. The data collection method used consists of observation, direct interviews with the principal and teachers. This research is supported by documentary data and supporting literature relevant to the problem described. This study uses qualitative descriptive analysis method with the aim of describing how the continuous professional development of SMA Negeri 1 Pandan Tapanuli Tengah teachers and how to deal with the problems faced in carrying out teacher sustainable professional development. The results of the study: 1) The self-development of teachers at SMA Negeri 1 Pandan has been carried out well with functional training activities and Teacher Working Groups (KKG); 2) Scientific Publications of SMA Negeri 1 Pandan Teachers, have been carried out well with three activities, namely, achievements in scientific forums, scientific publications in the form of research results or scientific ideas in the field of formal education and publication of textbooks, enrichment books or teacher manuals; 3) The innovative work of teachers of SMA Negeri 1 Matauli Pandan has run smoothly and optimally. Innovative work done by teachers makes learning media in the classroom. Teachers have made learning media that are used in the learning process